Risk of Congenital Anomalies in Pregnant Women with Type 2 Diabetes - Masood Ahmed, Mujeeb-Ur-Rehman Abro, Sania, Bushra Noor Khuhro, Farukh Imtiaz Bhanbhro, Abrar Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the risk of congenital anomalies in pregnant women with type II diabetes. Study design: Prospective study Place and duration of study: Department of Diabetes & Endocrinology, Chandka Medical College Hospital, Larkana from 1st October 2021 to 31st March 2022. Methodology: Two hundred pregnant women ≥20 weeks of gestation already suffering from type 2 diabetes were enrolled. Information in relation to their anomaly scan was gained through ultrasonography at the 20th to 21st week. The anomalies were identified as inconsequential (minor) and chief and correlated with the HbA1c percentage category. Results: There were 98 (49%) women who were nulliparous. The poor control as well as worst control HbA1C groups had highest value of body mass index. Within the congenital anomalies observed the overall rate of any anomaly was seen in patients with worst control while least number was observed in good control. Cardiovascular events followed by Genitourinary or renal issues were highest reported as congenital anomalies in fetus. Conclusion: There is a high risk of congenital anomalies in pregnant women with type 2 diabetes with cardiovascular anomalies to be the highest in category. HbA1C ≥11.5% and above is at highest risk of congenital anomalies. Keywords: Risk, Congenital anomalies, Pregnant woman, Type 2 diabetes